Identifikasi Bahaya dan Risiko di Laboratorium SMKN 1 Tanah Luas Menggunakan Metode HIRA - Sharie Suhaila Kyungsoo; Cut Aja Rahmahwati; Faridah Faridah (Jurnal Teknologi, 2023)
When carrying out practical activities carried out in the laboratory, the activity process does not always run as expected. There are times when the process experiences certain problems, one of which is that the practicum stops because the equipment is not functioning properly, causing accidents such as fires or explosions, students who carry out the practicum experience injuries that they get while carrying out the practicum in the laboratory. The purpose of risk assessment is to determine the possibility of occurrence and impact of an event that hinders the achievement of the organization's goals or objectives so that risks can be handled appropriately. This goal can be achieved through risk identification and risk analysis. The benefits of risk assessment include: helping to achieve organizational goals, maintaining continuity of service to stakeholders, providing services effectively and efficiently, being the basis for preparing strategic plans, and avoiding waste. The HIRA method was chosen because this method will identify, assess, and control dangerous risks that have the potential to occur in all work activities. This method can see how big the potential is and how serious it will be if the danger occurs. After identifying hazards using the HIRA method in the laboratory environment of SMK N 1 Tanah Luas. In calculating the level of possible hazards, the parameter for the frequency of occurrence of dangers in the High category is: every time the work is carried out. Medium category, namely: once in 10 to 100. Low category, namely once as long as the work is carried out.